1991
DOI: 10.1093/bja/67.3.235
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Comparison of the Morphine Sparing Effect of Continuous and Intermittent I.M. Administration of Ketorolac

Abstract: The morphine sparing effect of ketorolac 10 mg administered 4-hourly by intermittent i.m. injection was compared with a continuous i.m. infusion in a double-blind, placebo-controlled trial in patients undergoing upper abdominal surgery. During the 48-h postoperative period, each patient was provided with a patient-controlled analgesia (PCA) system which delivered bolus doses of morphine and administered the intermittent i.m. doses automatically via a computer controlled pump. In the first 24 h after surgery, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Ketorolac may therefore provide useful analgesia, either alone or as a supplement to an opioid, with minimal depressant effects. The analgesic effects of the ketorolac doses used in this study have been reported previously [2] and demonstrated the expected reduction in prostaglandin production by a significant decrease in postoperative morphine requirements.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ketorolac may therefore provide useful analgesia, either alone or as a supplement to an opioid, with minimal depressant effects. The analgesic effects of the ketorolac doses used in this study have been reported previously [2] and demonstrated the expected reduction in prostaglandin production by a significant decrease in postoperative morphine requirements.…”
Section: Discussionsupporting
confidence: 75%
“…Ketorolac trometamol is a new non-opioid analgesic of the non-steroidal anti-inflammatory (NSAID) class. It has been shown to provide a valuable morphine sparing effect when used to supplement opioid analgesia after upper abdominal surgery [1,2] and, in some studies, to have analgesic activity comparable to that of morphine [3,4]. Its principal advantage is lack of depression of the cardiovascular and respiratory systems [5].…”
mentioning
confidence: 99%
“…Furthermore, Burns et al [22] and Bosek and Miguel [23] reported that the use of ketorolac with opioids reduces opioid demand, which eventually decreases not only the incidences of hypoventilation, drug tolerance, and addiction but also the adverse effect of sedation. Also, in our study, which compared sedation scores measured in Group R and Group RK1, both of which showed statistically similar outcomes of pain control, Group RK1 revealed significantly lower scores.…”
Section: Discussionmentioning
confidence: 99%
“…The combined administration of COX inhibitors with opiates has been used either in animal research or in clinical trials in an attempt to enhance the antinociceptive activity of these drugs, but also to reduce the adverse effects produced by opiates, including the development of tolerance (Burns et al 1991; Sutters et al 1999; Gaitan et al 2003; Miranda et al 2005). It was of special interest to study the possible enhancement of analgesic activity of opiates combined with NO‐donor drugs, because it has been reported that a possible mechanism of action of the μ‐opioid agonist morphine involves stimulation of the cGMP system via NO release (Ferreira et al 1991).…”
Section: Pharmacologymentioning
confidence: 99%